The effects of hotel image, brand image and employee performance on customer satisfaction of Muslim youths towards Muslim-friendly hotels - Adnan, Nur Adilah; Abdul Latif, Samshul Amry (2018)
This paper aims to examine the effects of hotel image, brand image and employee performance on customer satisfaction of Muslim youths during their leisure stay in Muslim-Friendly (MF) hotels in Malaysia. Self-administered questionnaires measuring hotel image, brand image, employee performance and customer satisfaction on five-point Likert scale were distributed to 300 tourists in four prominent hotels in Kuala Terengganu. The data is then analyzed by multiple regression using SPSS software. The results indicated that hotel image and employee performance were found to be significant factors in predicting Muslim youth’s customer satisfaction of their hotel accommodation and hospitality services in MF hotels. However, brand image was found to be insignificant predictor to their satisfaction. The sample of this study was limited to only Muslims and they were mainly students. However, this does not suggest that students should be ignored in terms of their purchasing power and preference. Future studies may want to include other consumer segments and examine other MF hotels or hotels with similar concepts in countries interested to tap on the Muslim tourists, for example Japan, China and Korea among others. Malaysia is known to be a MF destination among tourists from many parts of the world. By understanding how Muslim consumers’ expectations, the performance of hotel employees and hotel image can be utilized by hotel operators to enhance their marketing strategies.